S48 Septal angle on mri predicts combined pre and post capillary pulmonary hypertension. (15th November 2017) - Johns, CS; Wild, JM; Rajaram, S; Tubman, E; Capener, D; Elliot, C; Condliffe, R; Charalampopoulos, A; Kiely, DG; Swift, AJ
Abstract : Patients with left heart disease commonly develop pulmonary hypertension (PH), and some subsequently develop pre-capillary vascular remodelling. This combined pre and post capillary pulmonary hypertension (Cpc-PH) is defined as mean pulmonary artery pressure (mPAP) ≥25 mmHg, pulmonary arterial wedge pressure (PAWP) >15 mmHg and diastolic pulmonary gradient (DPG) of ≥7. Patients with Cpc-PH, have a worse outcome and targeted pulmonary vascular therapies may be useful. The aim of this study was to assess MRI measured septal angle in the assessment of Cpc-PH. Methods: Consecutive, incident suspected PH patients who underwent MRI at a pulmonary hypertension referral centre from April 2012 to October 2015 were assessed. Patients with PAWP >15 mmHg, with right heart catheter and MRI on the same day were included. The diagnostic accuracy of septal angle to identify Cpc-PH was assessed. Results: 2437 patients underwent MRI, 1272 were incident and 227 patients had PAWP >15 mmHg. 163 had MRI and right heart catheter on the same date. The average age was 70 (sd 11), 64% were female. Systolic interventricular septal angle correlated with DPG (r=0.735, p<0.0001). ROC analysis showed septal angle was predictive of Cpc-PH (defined by DPG ≥7) with area under the curve 0.90 (p<0.0001). Analysis of the ROC data showed 160˚ septal angle as a threshold predicted a DPG of ≥7 mmHg, with 74% sensitivity and 90% specificity (p-value<0.0001). Systolic interventricular septal angle was predictive of outcome with univariate hazard ratio 1.017 (95% CI 1.007–1.028, p=0.001). Dichotomised by median value (149˚) the hazard ratio was 3.245 (95% CI 1.720–6.119, p<0.0001) and log-rank chi-square was 12.387. Conclusion: Interventricular septal angle on MRI can non-invasively predict the presence of an elevated diastolic pressure gradient in patients with left heart disease.